2010
DOI: 10.1002/app.32993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recrystallization on the molecular mobility of a copolymer of vinylidene fluoride and hexafluoropropylene

Abstract: Relaxation processes in copolymers of vinylidene fluoride with hexafluoropropylene (93/7) were studied by means of a dielectric method. The initial extruded film was recrystallized by free heating to temperatures above the melting point and by subsequent cooling. This increased both the perfection of the crystal phase and the degree of crystallinity. The impact of recrystallization on both the relaxation times (s's) and the activation parameters of the local mobility (b process) and microBrownian cooperative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
(83 reference statements)
2
4
0
Order By: Relevance
“…The dielectric permittivity of P(VDF- co -HFP) at temperatures higher than T g , that is, in the temperature range of −20 °C to 40 °C, increases with increasing temperature and decreasing frequency. At room temperature, it amounts to around 8 at 1 kHz ( Figure 6 a), which is consistent with the values known from the literature ( ε ′~10), depending on the HFP content in the P(VDF- co -HFP) copolymer [ 52 , 55 , 56 ]. This permittivity increase is attributed to the enhanced segmental motions of dipole units within P(VDF- co -HFP), associated with both α a and α c relaxation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The dielectric permittivity of P(VDF- co -HFP) at temperatures higher than T g , that is, in the temperature range of −20 °C to 40 °C, increases with increasing temperature and decreasing frequency. At room temperature, it amounts to around 8 at 1 kHz ( Figure 6 a), which is consistent with the values known from the literature ( ε ′~10), depending on the HFP content in the P(VDF- co -HFP) copolymer [ 52 , 55 , 56 ]. This permittivity increase is attributed to the enhanced segmental motions of dipole units within P(VDF- co -HFP), associated with both α a and α c relaxation.…”
Section: Resultssupporting
confidence: 90%
“…The real part of the dielectric function, or permittivity, ε ′, has a point of inflection at the lowest frequencies, connected to an additional relaxation process, known as α c relaxation. This process is related to relaxation occurring within the crystalline phase of P(VDF- co -HFP), and shows up at temperatures around 0 to 40 °C [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…As appears from Figure 7b, annealing in the continuous heating mode to 200 ºС is accompanied by appreciable change of diffraction curves, especially for intramolecular order (larger s). As it is earlier noted on copolymers VDF with hexafluoropropylene (Kochervinskii, 2011), the additional peaks are observed in a film after recrystallization. The changes occur in some structural parameters after the recrystallization in as shown in the table.…”
Section: Discussionsupporting
confidence: 74%
“…More recently, Kochervinski et al [99] reported the ferroelectric behaviour of typical P(VDF‐TFE)94/6 mol% copolymers, which is found that the copolymer looks like a linear dielectric whose permittivity nonlinearly increases with the amplitude of the alternating field in low fields, as shown in Fig. 19.…”
Section: Pvdf Homopolymer Dielectrics and Their Applicationsmentioning
confidence: 99%
“…Changes in the shape of the dielectric-hysteresis loop with variation in the amplitude of the external field of P(VDF-TFE)94/6 mol%[99] Schematic configuration of PVDF sensor[10β] …”
mentioning
confidence: 99%